Specific Growth Rate of Chlorella sp. And Dunaliella sp. According to Different Concentration of Nutrient and Photoperiod - Mujizat Kawaroe; Tri Prartono; Adriani Sunuddin; Dahlia Wulan Sari; Dina Augustine (Jurnal Ilmu-Ilmu Perairan dan Perikanan Indonesia, 2009)
Light and nutrient are factors that support the microalgae growth rate besides COB2B, temperature, and salinity. Microalgae growth of Chorella sp. and Dunaliella sp. were observed to determine the influences of different nutrient concentration and photo period. Microalgae cultivation was located at laboratory using 100 mL Erlenmeyer. The specific growth rate of microalgae was observed for different nutrient concentration and photo period of light treatments. Using Guillard/f2 nutrient, the highest specific growth rate for Chorella sp. was 0.227/d and 0.289/d for Dunaliella sp. The highest microalgae specific growth rate influenced different photo period was 0.39/d and 0.329/d, respectively. Finally, the highest specific growth rate for both cultivated species of microalgae was observed at 2V nutrient concentration and 24 hour period of light treatment.Keywords : Spesific growth rate, photoperiod, nutrient, Chlorella sp., Dunaliella sp.